2021
DOI: 10.1111/gcb.15864
|View full text |Cite
|
Sign up to set email alerts
|

Mapping soil microbial residence time at the global scale

Abstract: Soil microbes are the fundamental engine for carbon (C) cycling. Microbial residence time (MRT) therefore determines the mineralization of soil organic C, releasing C as heterotrophic respiration and contributing substantially to the C efflux in terrestrial ecosystems. We took use of a comprehensive dataset (2627 data points) and calculated the MRT based on the basal respiration and microbial biomass C. Large variations in MRT were found among biomes, with the largest MRT in boreal forests and grasslands and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 101 publications
2
13
0
Order By: Relevance
“…S15). The map did not reveal notable latitudinal trends, unlike other soil C processes, such as soil respiration (Xu et al ., 2013), bacterial and fungal biomass (He et al ., 2020), and microbial residence time (He & Xu, 2021). However, it highlighted four hotspots of soil algal NPP (> 50 g C m −2 yr −1 ), in northeastern North America, southeastern South America, central and western Europe, and eastern Asia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S15). The map did not reveal notable latitudinal trends, unlike other soil C processes, such as soil respiration (Xu et al ., 2013), bacterial and fungal biomass (He et al ., 2020), and microbial residence time (He & Xu, 2021). However, it highlighted four hotspots of soil algal NPP (> 50 g C m −2 yr −1 ), in northeastern North America, southeastern South America, central and western Europe, and eastern Asia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified climate factors (temperature and moisture; Reinsch et al, 2013), plant properties (i.e., litter quality and quantity; Fanin et al, 2020;Pascault et al, 2013), soil properties (SOC content and stability, pH; Bastida et al, 2019;Chen et al, 2018Chen et al, , 2019, and microbial attributes (microbial biomass, diversity, and community structure; Fontaine et al, 2003;Liang et al, 2018;Razanamalala et al, 2018) as potential drivers of soil priming effects. Despite these findings providing useful information on the environmental drivers of soil priming effects across local and regional-biome, a systematic and holistic understanding of soil biogeography of priming effects and their dominant drivers is lacking at the global scale (Guenet et al, 2018;He & Xu, 2021;Wieder et al, 2013). Moreover, it is widely accepted that the direction and intensity of soil priming effects are regulated by a succession of processes rather than singular mechanisms (Kuzyakov et al, 2000), the fresh C input-induced soil priming effect is a general phenomenon that occurs in various terrestrial ecosystems involving diverse substrates, but we are still lacking a simple and generalizable framework to explain this important soil process (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the difference in substrates and microbial properties can partly explain the inconsistent seasonal pattern between MBC and Rh by latitude. The distinct microbial turnover rates ( 36 ), soil organic carbon chemical composition ( 37 ), and substrate use efficiency ( 38 ), and their differences in seasonal variations can partly explain the discrepancy between MBC and Rh along latitude. Third, vegetation labile C input plays an important role in determining the inconsistent seasonal patterns between MBC and Rh.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, different responses of microbial biomass maintenance and respiration to environmental change may account for the inconsistent seasonality between MBC and Rh. For example, microbial turnover and respiration are temperature-sensitive; both are enhanced by rising temperature ( 36 , 44 , 45 ). Although soil microbes are major drivers of Rh, the tradeoff between soil microbial biomass maintenance and respiration can partially explain the seasonal inconsistency between MBC and Rh.…”
Section: Discussionmentioning
confidence: 99%